2022
DOI: 10.24093/awej/vol13no3.34
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Foreign Language Apprehension and Foreign Language Gaiety and their Impacts on the Ideal L2 Self for EFL Learners

Abstract: As evidenced by recent studies in the fields of positive psychology and psycholinguistics, learners’ emotions and thoughts while learning a second language are believed to generate sophisticated and dynamic linkages that contribute to their motivational as well as linguistic outcomes. This study aims to evaluate foreign language gaiety (FLG) and foreign language apprehension (FLA) as determinants of the ideal second language (L2) self for Saudi EFL learners. The basic research question that this study attempts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Haghparast and Mall-Amiri (2015) asserted that EFL students can support one another in the same way that instructors help the students by expanding the scaffolding framework. The answer to this study question is in line with earlier scholarly studies (M. A. Abdulaal et al, 2022c; Hamidi & Bagherzadeh, 2018; Harraqi, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Haghparast and Mall-Amiri (2015) asserted that EFL students can support one another in the same way that instructors help the students by expanding the scaffolding framework. The answer to this study question is in line with earlier scholarly studies (M. A. Abdulaal et al, 2022c; Hamidi & Bagherzadeh, 2018; Harraqi, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…To improve the learners' speaking abilities, some achievementbased assessments were included in their study. Additionally, a study conducted concluded that achievement-based assessment improved EFL students' listening comprehension (Abdulaal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…According to Arnold (2007), foreign language apprehension is a circumstance-specific phenomenon brought on by foreign language acquisition in an official setting, particularly when one's own perception of one's communicative proficiency in the target language is low. Abdulaal et al (2022) presented three components of foreign language anxiety in a similar vein (i.e., communicative fear, test apprehension, and fear of assessment). The first component, communicative fear, deals with issues with oral communication, listening comprehension, or social anxiety.…”
Section: Foreign Language Apprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the instructors and the students read poetic verses, language structure should be taken into consideration. Besides, considering sentence structure leads to the realization that grammatical patterns are shared by all languages and dialects (Abdulaal, Sadek, Ageli, Al-Hawamdeh, & Hal, 2022).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%